Peran Operator Sekolah dalam Pengelolaan Administrasi Pendidikan di SD Negeri 1 Ubung Kabupaten Lombok Tengah - Ni Desak Made Kartini Dwitya; Mohamad Mustari (Action Research Journal, 2026)
This research aims to describe the role of school operators in managing educational administration at Ubung 1 Public Elementary School. The focus of the study is directed at the role, task implementation, and contribution of school operators in supporting the smooth running of technology- and data-based educational administration. This study uses a qualitative approach with descriptive methods, aiming to obtain an in-depth overview of the phenomena occurring naturally in the field. Data collection techniques were conducted through observation, interviews, and documentation, involving school operators as the primary subjects and the principal and teachers as supporting informants. Data analysis techniques were implemented in three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that school operators play a very significant role in managing educational administration at Ubung 1 Public Elementary School. School operators are responsible for updating the basic education data (Dapodik), managing and archiving school administrative documents, providing academic and administrative information to teachers and parents, and managing the school’s information technology-based administration system. The existence of school operators also plays a role in increasing the effectiveness, efficiency, and accuracy of educational administration management, thus supporting the school’s decision-making process